KONSEP PENDIDIKAN AKHLAK PERSPEKTIF JALALUDDIN RUMI (Analisis Buku Fihi Ma Fihi Serta Relevansinya Terhadap Pendidikan Islam) - Moh Ali (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2021)
The book Fihi Ma Fihi is one of the master pieces of a Sufi figure named Jalaluddin Rumi, which contains Rumi's lectures in prose. Contains lecture materials, reflections, and comments that discuss issues surrounding morals which are complemented by interpretations of the Koran and Hadith. The formulation of the problems in this study are: 1). How is the concept of moral education from the perspective of Islamic education? 2). What are the values of moral education contained in the book Fihi Ma Fihi by Jalaluddin Rumi? 3). How is the relevance of the value of moral education in the book Fihi Ma Fihi to Islamic Education? This research is a qualitative research in the form of descriptive and the type of research is library research. The object of research in this thesis is a literary work in the form of a book entitled Fihi Ma Fihi Karya Jalaluddin Rumi. The approach taken by the author to obtain data is to search for books that are relevant to the object of study with primary data sources coming from the book Fihi Ma Fihi. The method used by the author in this thesis is the documentary method, which is looking for variable data in the form of notes, manuscripts, book transcripts and so on. This study uses a qualitative descriptive analysis technique. Based on the analysis conducted by the author, it can be concluded that: 1). The values of moral education in the book Fihi Ma Fihi include Love, Khauf and Raja ', Tawakal, Ikhlas, Muraqabah, Dhikr to Allah, Istikamah, Tawadu', Patience, Mujahadah, Forgiveness and Glorification of others. 2). The value of moral education in Jalaluddin Rumi's book Fihi Ma Fihi can be reflected in the process of spiritual education in humans so that they follow what Allah, the Lord of the universe and the universe wants. It is the process of achieving the perfection of human spiritual potential which is shown by the attainment in the form of spiritual cleanliness, breadth in thinking, depth of understanding of knowledge, the virtue of morals, which leads people to God. Buku Fihi Ma Fihi merupakan salah satu master piece dari seorang tokoh sufi bernama Jalaluddin Rumi, yang memuat ceramah-ceramah Rumi dalam bentuk prosa. Berisi tentang materi perkuliahan, refleksi, dan komentar yang membahas tentang masalah seputar akhlak yang dilengkapi dengan tafsiran Al-Quran dan Hadis. Rumusan masalah dalam penelitian ini adalah: 1). Bagaimana konsep pendidikan akhlak perspektif pendidikan Islam? 2). Bagaimana nilai-nilai pendidikan akhlak yang terkandung dalam buku Fihi Ma Fihi karya Jalaluddin Rumi? 3). Bagaimana relevansi nilai pendidikan akhlak pada buku Fihi Ma Fihi terhadap Pendidikan Islam? Penelitian ini termasuk penelitian kualitatif yang berbentuk deksriptif dan jenis penelitiannya adalah kepustakaan (library research). Objek penelitian dalam tesis ini adalah karya sastra berupa buku yang berjudul Fihi Ma Fihi Karya Jalaluddin Rumi. Pendekatan yang dilakukan oleh penulis untuk memperoleh data adalah dengan mencari buku-buku yang relevan dengan obyek kajian dengan sumber data primer berasal dari buku Fihi Ma Fihi. Metode yang dilakukan penulis dalam tesis ini adalah metode dokumenter yakni mencari data variabel yang berupa catatan, naskah, transkip buku dan sebagainya. Penelitian ini menggunakan teknik analisis deskriptif kualitatif. Berdasarkan analisis yang dilakukan penulis dapat disimpulkan bahwa: 1). Nilai-nilai pendidikan akhlak pada buku Fihi Ma Fihi meliputi Cinta, Khauf dan Raja’, Tawakal, Ikhlas, Muraqabah, Berdzikir kepada Allah, Istikamah, Tawadu’, Sabar, Mujahadah, Memaafkan dan Memuliakan terhadap sesama. 2). Nilai pendidikan akhlak dalam buku Fihi Ma Fihi karya Jalaluddin Rumi dapat tercermin dari proses pendidikan rohani pada manusia agar ia mengikuti apa yang dikehendaki Allah, Tuhan semesta dan jagat raya ini. Merupakan proses pencapaian kesempurnaan potensi spiritual manusia yang ditunjukan dengan pencapaian dalam wujud kebersihan rohani, keluasan dalam berpikir, kedalaman pemahaman ilmu, keutamaan akhlak, yang membawa manusia menuju kepada Tuhan.